Hyperinfection by Strongyloides stercoralis: Series of Cases in a Regional Hospital in Southern Spain - Ana Lucas-Dato; María Dolores Hernández-Rabadán; Pedro Luis Boils Arroyo; Jara Llenas-García (Microbiology Research)
Background: Strongyloidiasis is a neglected tropical disease caused by the nematode Strongyloides stercoralis. In immunosuppressed patients, it may progress to hyperinfection syndrome (HIS) and disseminated strongyloidiasis (DS), both of which are associated with high mortality rates. We reviewed cases of HIS and DS in a Spanish hospital located in an area with endemic strongyloidiasis. Methods: All of the patients who met the HIS or DIS criteria between 1999 and 2023 at the Vega Baja Hospital in Orihuela (Alicante, Spain) were included. Results: Five patients were identified, four of them autochthonous (median age 72 years, 80% male), with three cases of HIS and two cases of DS in the form of meningitis, due to E. faecalis and E. coli. The most common risk factor, observed in three patients, was corticosteroid use. Two patients died. Conclusions: This case series highlights the severity of infections in immunocompromised patients in an endemic area of Spain, emphasizing the need to establish screening protocols for patients at risk of immunosuppression, including both locals and migrants.